Misinformation in Germany During the Covid-19 Pandemic - Christina Leuker; Lukas Maximilian Eggeling; Nadine Fleischhut; John Gubernath; Ksenija Gumenik; Shahar Hechtlinger; Anastasia Kozyreva; Larissa Samaan; Ralph Hertwig (University of Zurich, IKMZ - Department of Communication and Media Research, 2022)
During the Covid-19 pandemic, people have been exposed to vast amounts of misinformation. This "infodemic" has undermined key behavioural and pharmacological measures to contain the pandemic. In a cross-sectional survey of residents of Germany, we investigated the perceived prevalence of misinformation, the strategies people reported using to discern between true and false information, and individual differences in beliefs in misinformation at three time points from June 2020 to February 2021 (N = 3324). We observed four main results. First, there was an increase in the perceived prevalence of misinformation over time. Second, the most believed false claims included that the virus is no worse than the flu and that the EU has approved dangerous vaccines. Third, belief in misinformation was associated with support for the far-right AfD party; reliance on tabloids, neighbours and social media for information; lower levels of education; and migration background. Fourth, only about half of the respondents reported using strategies such as checking for consistency between different sources to identify misinformation. These results can inform the development of interventions, such as boosting the ability to discern accurate from misleading information, or enriching specific environments (e.g., neighbourhoods with high rates of migration) with accessible and high-quality information.